(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the current antibiotic resistance situation of S. aureus at Nghe An Obstetrics and Pediatrics Hospital. Subjects-methods: Cross-sectional description of specimens: blood, sputum, urine, body fluids, and pus from the patients diagnosed with infection who came for examination and treatment at Nghe An Obstetrics and Pediatrics Hospital from January 2021 to January 2022. Results: S. aureus is strong resistant to many antibiotics, including benzylpenicillin (98.4%), clindamycin (81.5%), erythromycin (81.5%), tetracycline (77.2%). MRSA is also more resistant to other antibiotics than MSSA. The rate of resistance of MRSA to the benzylpenicillin, clindamycin, ciprofloxacin, erythromycin, oxacillin, rifampicin, tetracycline was higher than that of MSSA and this difference was statistically significant (p <0.05). Both MRSA and MSSA were not resistant to vancomycin, linezolid, quinupristin/dalfopristin, rifampicin, nitrofurantoin…; The rate of multiantibiotic resistance over 3 types in MRSA strain was 97%, MSSA strain 27.3%. Conclusions: In addition to antibiotic combinations to treat MRSA, the new treatment options using other antibiotics are gradually emerging, using a combination of affordable and affordable antibiotics is the method, the only promising alternative for MRSA-like bacterial infections.